2010
DOI: 10.1186/1465-9921-11-21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PPARγ ligands on TGF-β1-induced epithelial-mesenchymal transition in alveolar epithelial cells

Abstract: BackgroundTransforming growth factor β1 (TGF-β1)-mediated epithelial mesenchymal transition (EMT) of alveolar epithelial cells (AEC) may contribute to lung fibrosis. Since PPARγ ligands have been shown to inhibit fibroblast activation by TGF-β1, we assessed the ability of the thiazolidinediones rosiglitazone (RGZ) and ciglitazone (CGZ) to regulate TGF-β1-mediated EMT of A549 cells, assessing changes in cell morphology, and expression of cell adhesion molecules E-cadherin (epithelial cell marker) and N-cadherin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 55 publications
(89 reference statements)
2
70
0
Order By: Relevance
“…A549 cells demonstrated many features of AECII cells [32], and most studies investigating EMT have used A549 cells as a model of AECII [30,31,[33][34][35]. In addition, a few studies have used both A549 cells and primary AECIIs to study EMT and showed that A549 cells presented similar features as primary AECIIs during the EMT process [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…A549 cells demonstrated many features of AECII cells [32], and most studies investigating EMT have used A549 cells as a model of AECII [30,31,[33][34][35]. In addition, a few studies have used both A549 cells and primary AECIIs to study EMT and showed that A549 cells presented similar features as primary AECIIs during the EMT process [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Interfering with Smad3, PPAR and its ligands suppress CTGF expression in response to TGF- 46,47) . Our study demonstrates that overexpression of Runx2 blunted the TGF-induction of CTGF expression.…”
Section: Runx2 Inhibits Tgf--induced Ctgf Expression By Interacting Wmentioning
confidence: 99%
“…2) This cytokine also drive EMT. 20,21) Besides, persistence of TGF-b1 expression counters the apoptosis of fibroblast by inducing activation of the adhesion-dependent focal adhesion kinase pathway and the soluble growth factor-mediated AKT pathway. 22,23) Other studies found that the aqueous extract of safflower (40 mg/ml) had anti-proliferative and pro-apoptotic effects on hepatic stellate cells that play a central role in hepatic fibrosis, 13) and it (150 mg/3 ml/0.25 kg/d) also could reduce serum TGF-b1 of unilateral ureteral obstruction-induced renal interstitial fibrosis in rats.…”
Section: Discussionmentioning
confidence: 99%